Speech Delay and Excessive Gadget Usage: Understanding Pathophysiology Mechanism and Prevention Target Among Children Population - Jopi Chandra Sindhutomo (Eduvest - Journal of Universal Studies, 2024)
In this state of modern era, usage of electronic gadget has increased excessively with the last ten years. Usage of devices has increased especially among children and adolescent population as a form for information display, education, and entertainment. Problems that arise of electronic gadget usage among children and adolescent population is excessive usage, which defined as usage of gadget over two hours per day. The huge pitfall of this phenomenon is the increasing incident of developmental delay within children population, specifically speech delay. Speech delay development found to be high prevalent in children under five years old, and there are several studies that have discussed correlation between speech delay and excessive usage of gadget. These studies have found that speech delay that led by excessive usage of gadget could occur due to understimulation of certain brain regions that involved in words sensory and recognition, and speech motoric ability, especially during neurodevelopmental period. Understanding of pathophysiology mechanism between speech delay and excessive gadget usage is important for every healthcare provider to educate family and creating preventive strategies from individual, family, and community aspect.